Distribution and genetic characterization of bird rape mustard (Brassica rapa) populations and analysis of glyphosate resistance introgression. Issue 12 (28th September 2022) - Laforest, Martin; Martin, Sara; Soufiane, Brahim; Bisaillon, Katherine; Maheux, Lydia; Fortin, Sylvain; James, Tracey; Miville, David; Marcoux, Annie; Simard, Marie‐Josée
Abstract: Background: The introgression of a transgene conferring glyphosate resistance from Brassica napus (rapeseed, canola) to Brassica rapa weeds (bird rape) was documented at a single location in 2007. In 2015, several cases of glyphosate resistant mustard were reported by growers in areas where rapeseed was seldom grown. Results: Survey result indicated glyphosate resistant bird rape mustard is present in areas where glyphosate tolerant corn and soybean are often grown in rotation. Genetic analyses reveal that hybridization followed by introgression and progressive loss of chromosome is the likely mechanism for the horizontal gene transfer (HGT) of glyphosate resistance. Conclusion: Introgression of the glyphosate‐resistance conferring transgene in the populations studied appears to have occurred several times, consistent with the ease for B. rapa to form hybrids with B. napus . The introduction of a transgene into a crop should therefore take into account the weediness of the species that share a common genome and their ability to form hybrids. We provide here such an example between B. napus and B. rapa, and potentially between B. napus and Raphanistrum raphanistrum . © 2022 Her Majesty the Queen in Right of Canada. Pest Management Science © 2022 Society of Chemical Industry. Reproduced with the permission of the Minister of Agriculture and Agri‐Food Canada. Abstract : The transgene conferring resistance to glyphosate was introgressed into bird's rape ( Brassica rapa ) from cultivated canola ( Brassica napus ). Here we report the genetic analysis and distribution of suspected glyphosate resistance brassica rapa weeds surveyed in producer fields.